The oldest pottery of the Para-Neolithic Zedmar culture at the site Szczepanki, Masuria, NE-Poland - Witold Gumiński (Documenta Praehistorica, 2020)
The article presents the earliest ceramics of the site Szczepanki, north-eastern Poland, belonging to the Para-Neolithic Zedmar culture, which existed in the south-east Baltic region. The presented pottery come from the Late Atlantic layers, dated 5600–5100 conv BP. The pottery is discussed regarding the technology, morphological details, vessel forms and ornamentation. Each of the elements shows multidirectional influences or similarities with the Western and the Eastern Para-Neolithic, as well as the Danubian cultures and the TRB. However, a specific characteristic of the early Zedmar pottery relies on mixing features of various origins or traditions, creating a new and peculiar technology and style.